Functional roles of Speckle-Type Poz (SPOP) Protein in Genomic stability - Wei, Xi (J Cancer, 2018)
Understanding the functional significance of the essential elements in maintaining genomic stability provides insights into the process of tumor initiation and progression, and predicts therapeutic responses. One such element that has recently attracted significant attention is the Speckle-Type Poz Protein (SPOP), an E3 ubiquitin ligase adaptor protein. SPOP is frequently mutated or has altered expression in various cancers, including prostate, renal and endometrial. SPOP is involved in the regulation of proteasome-mediated degradation of several oncoproteins. Moreover, recent data also indicate SPOP's direct involvement in the DNA damage response. SPOP mutants induce alternations in the DNA damage repair pathway by promoting the error-prone Non-homologous end joining (NHEJ) pathway. SPOP has been linked with significant functions in cellular signaling pathways and cancer suppression. This mini-review will discuss recent findings regarding SPOP's role in genomic stability in the pathological setting.